Chronology and documentary handbook of the State of Wyoming - Vexler, Robert I. (Dobbs Ferry, N.Y. : Oceana Publications, 1979)
Contains a chronology of events in Wyoming from 1742 to 1977, biographical sketches of prominent citizens, and selected documents pertinent to Wyoming history.
Cover title: Wyoming, a chronology & documentary handbook.
Includes index.
Bibliography: p. 147.
Keywords: Wyoming -- History -- Chronology; Wyoming -- Biography; Wyoming -- History -- Sources; Wyoming -- History